Nisha-Amalaki in Uncontrolled Type 2 Diabetes Mellitus- A Case Report (International Journal of Ayurveda and Pharma Research, 2022)
During the last few years India has maximum increase of Type 2 diabetes mellitus. Type 2 diabetes is characterized by high blood sugar, insulin resistance, and relative lack of insulin. There are approximate 72.96 million cases of diabetes mellitus in adult population of India. In modern era single anti-diabetic drug is not sufficient for glucose control. These days multidrug therapy is building its popularity for maintaining glycaemic levels. A 59-year-old female presented with known case of Type 2 diabetes with evidence of polyuria, itching over extremities, and fatigue was poorly controlled despite a drug regimen consisting of oral metformin and glimepiride. Her Blood Sugar level was constantly around 200 mg/dl in spite of having modern medicine with adjusted doses. She has administered Nisha-Amalaki Churna with warm water early in the morning along with standard conventional treatment for 8 weeks. The effect of therapy was evaluated at the interval of 4 weeks for 8 weeks which is done on the basis of objective parameters. Objective parameters were fasting and post prandial Blood Sugar Level. Nisha-Amalaki churna has reduced Blood Sugar Level to normal. It also reduced the dose of conventional drug which may cause side effects with long term use. There is a need for combined multidisciplinary treatment to maintain suggested glycaemic control. Thus, the present case study is to understand the significant effect of Nisha-Amalaki as an adjuvant to standard conventional treatment in chronic uncontrolled type 2 Diabetes Mellitus.